FEATURES OF SELF-ACTUALIZATION OLDER TEENS - Sydorchuk, Maryna S. (Educological discourse, 2015)
The article describes the features of the process of self-actualization older teens. The theoretical analysis approaches in the literature to the definition of older adolescents and self-actualization in older teens. The basic principles to be followed when forming ability of adolescents to self-actualization, the author’s definition of «self-actualization older teens».